2017
DOI: 10.3168/jds.2017-12839
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Cow- and quarter-level milking indicators and their associations with clinical mastitis in an automatic milking system

Abstract: The aim of this study was to assess associations of cow-, udder-, and quarter-level factors with the risk of clinical mastitis (CM) in cows managed using an automatic milking system. The primary hypothesis was that quarter peak milk flow rate (QPMF) is associated with increased risk of CM. A retrospective, case-control study was undertaken using data from a 1,549 cow farm using 20 automatic milking system units. All data from cows milked during March to December 2015 was available for analysis. Cases (n = 82) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Data from electronic on-farm milk meters that routinely measure milking characteristics have been established as measures of parlor performance (Reid and Stewart, 2007;Treichler and Reid, 2013), premilking udder preparation (Watters et al, 2012(Watters et al, , 2015, and assessment of liner performance . In addition, recent case-control studies have investigated the association of milking characteristics with the risk of clinical mastitis (Guarín and Ruegg, 2016;Penry et al, 2017a). However, the association with machine milking-induced short-term changes remains to be investigated.…”
Section: Short Communicationmentioning
confidence: 99%
“…Data from electronic on-farm milk meters that routinely measure milking characteristics have been established as measures of parlor performance (Reid and Stewart, 2007;Treichler and Reid, 2013), premilking udder preparation (Watters et al, 2012(Watters et al, , 2015, and assessment of liner performance . In addition, recent case-control studies have investigated the association of milking characteristics with the risk of clinical mastitis (Guarín and Ruegg, 2016;Penry et al, 2017a). However, the association with machine milking-induced short-term changes remains to be investigated.…”
Section: Short Communicationmentioning
confidence: 99%
“…This is another factor that increases the danger of infection of teats when using poor-quality milking rubber, in addition to the increased bacterial insemination. It was established in [9] that using the milking rubber that had lost its primary technological indicators such as elasticity, elasticity, integrity, etc., increases the likelihood of slipping off of the suspension part of the machine. An incomplete milking increases the propensity of teats to accept new infectious agents.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Previous studies have shown that the use of only EC in different detection algorithms was unable to achieve the ISO (2007) standard Se (>70%) and Sp (>99%) for CM detection (Khatun et al, 2017). In the past decade, many attempts have been made to improve the Se and Sp of CM detection using AMS data; however, they were not successful enough to detect at quarter level, and the search for an improved automated mastitis detection system continues (Claycomb et al, 2009;Hogeveen et al, 2010;Penry et al, 2017). Moreover, in a pasture-based AMS, where cows are less visible to the farmers compared with an indoor farming system, checking multiple alerts (either automatic or nonautomatic) to improve Se and Sp for detection of mastitis requires an increase in workload .…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by the effect of temperature, fat content, or milk fraction on EC measurements (Nielen et al, 1992;Bruckmaier et al, 2004). The decreasing trend (<0.429 mS/cm per hour, opposite to EC) of the ECH for the CM alert might be related to milking interval as mastitic cows are prone to have longer milking intervals, allowing longer harboring of the pathogens causing infection (Hogeveen et al, 2001;Hammer et al, 2012;Penry et al, 2017). Similar to a recent report by another group, our study did not find strong CM prediction ability of PF, which is considered an important breeding parameter (Penry et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation